Impacto da satisfação no trabalho e da percepção de suporte organizacional sobre a Síndrome de Burnout em trabalhadores de enfermagem de um Hospital Universitário - Neves, Vanessa Faria (2012)
The syndrome has been identified as a social problem of importance and has been investigated in several countries, since it is bound to organizational costs. Burnout is defined as a psychological syndrome from chronic emotional stress experienced at work that had resulted from the emotional exhaustion dimensions, cynicism, or dehumanization, and disappointment at work, also called decreased personal accomplishment or inefficacy. This study proposes to investigate a model in which the variables job satisfaction and organizational support perceived consist of predictors of Burnout syndrome in nursing professionals. The study sample consisted of 339 nursing staff of a university hospital (36,6% nursing technicians, 31,9% nurses and 31,6% nursing assistants), and 81,1% females, mean age of 38.7 years and average of 14.4 years of completion of course. The participants answered a questionnaire composed of social-demographic data and the validated scales of Job Satisfaction, Organizational Support Perceived (EPSO) and Characterization of Burnout Scale (ECB). The data were analyzed using SPSS software, version 12.0, through which were calculated statistics descriptive, Cronbach\'s alpha for the study sample and regression multiple analysis (stepwise method), and job satisfaction (five dimensions) and organizational support perceived the independent variables. The indices of reliability for the scales were satisfactory, ranging from 0.73 to 0.94. The results indicated that for emotional exhaustion dimension have three predictors, namely: satisfaction with the nature of work with the highest percentage of explained variance (29%), organizational support perceived (5%) and satisfaction with salary (1%). The size of dehumanization was just satisfaction background with the nature of work and 7% of explained variance and the organizational support perception that was explained by 2% of variance. In their turn, the disappointment work size, showed like predictors the satisfaction with the work nature (28%), organizational support perceived (7%) and satisfaction with promotion (1%). Therefore, the highest percentages of explanation for the three dimensions of Burnout syndrome were attributed to satisfaction with the nature of work and organizational support perceived, demonstrating the importance of health organizations to establish strategies for appreciation of nursing professionals, as well as support and management activities material undertaken by these workers. Future studies should be conducted to confirm the data on other organizations and health professional, because the prevention of this syndrome is essential to ensuring a quality to users of the health care services.